BNK 48 a Thai-Japanese cultural commodity in the stagnation of Thai music business: Contemporary entertainment business history - DOME KRAIPAKORN (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This article explores the meteoric rise of the BNK48 music group in Thailand from late 2017 to the present (early 2018), especially in light of the relatively sluggish state of Thailand’s music industry.Method: The study takes a retrospective look at the rise to fame of BNK48 by analysing interviews with the group’s members and management team that were published in periodicals and fanzines.Findings: Purchases made for reasons other than practical use can be considered cultural commodity consumption. The success of the idols who share their interests in cartoons, games, and cosplay, as well as the self-improvement efforts of the idols, which is the value attached to the stories, are consistent with the cultures and feelings of young people in the late 2000s, could be seen as the reason "otakus" buy BNK48 products.Implications/Novel Contribution: Through an in-depth analysis of the cultural and emotional ties BNK has forged with its adherents, the current body of research points the way to a body of literature.